ANALISIS KELAYAKAN FINANSIAL PENGEMBANGAN EKOWISATA HIU PAUS (Rhincodon typus) DI KECAMATAN TALISAYAN KABUPATEN BERAU - Mega Saparinah; Bambang Indratno Gunawan; Qoriah Saleha (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
The purposes of this study were to determine the perceptions of the public and tourists on the Whale Shark ecotourism development project (Rhincodon typus), to identify the costs and benefits of the Whale Shark ecotourism development project (Rhincodontypus), to assess the financial feasibility of Whale Shark ecotourism (Rhincodontypus) based on investment criteria that include Net The Present Value, Internal Rate Of Return, Net BC Ratio and Payback Period, identify the main problems that occur in Whale Shark ecotourism (Rhincodontypus) in Talisayan Subdistrict, Berau District. The sampling method used was a purposive sampling method with 30 respondents. The method of data analysis uses descriptive methods based on graphs and financial feasibility analysis. The results of this study indicated that the perception of the community and tourists towards the development of ecotourism of the whale shark (Rhincodon typus) is that strongly agree with the existence of the project. The costs of infrastructure development projects for the development of ecotourism of the Whale Shark (Rhincodon typus) namely investment and operational costs consist of fixed costs and variable costs, where as the benefit of the project in economic terms can open up new jobs for local communities. In the mean while, the village popularity is becaming more famous around local tourist and foreign tourist. Infrastructure development projects for the development of the Whale Shark (Rhincodon typus) ecotourism with Net Present Value investment criteria of Rp.257,559,474, Internal rate of Return of 13%, Net Benefit Cost Ratio of 1,434 and Payback Period of 3 years are feasible to run. The problems were the access road to the location of the Whale Shark (Rhincodon typus) ecotourism and poor lighting on the road.